Pengaruh Model Pembelajaran terhadap Motivasi Belajar Siswa SMK: Studi Meta Analisis - Surachman, Muhammad Ilham; Iskandar, Ranu; Naryanto, Rizqi Fitri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The purpose of this study is to conduct a meta-analysis that measures the influence of several learning models such as cooperative learning, project-based learning, and problem-based learning. Data were collected from previous articles gathered through Google Scholar and Semantic Scholar. Keywords used combinations of learning models, cooperative learning, project-based learning, problem-based learning, learning motivation, learning motivation, and vocational high school (SMK). This meta-analysis research follows the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Data processed using JASP software included effect size and standard error to generate forest plots. The analysis results show an effect size value of 0.579, which means there is a quite significant influence between learning models and vocational high school students' learning motivation. Analysis by field of expertise shows results for information technology (0.704, 95% CI -0.369, 1.778), manufacturing and engineering technology (0.651, 95% CI -0.671, 1.972), and business and management (0.164, 95% CI -0.904, 1.232) are not yet significant because the p-value > 0.05. Analysis of learning model variables shows problem-based learning (0.338, 95% CI -0.709, 1.384), project-based learning (-0.283, 95% CI -1.377, 0.810), and cooperative learning (-0.356, 95% CI -2.095, 1.382) are less significant with p > 0.05. These results indicate that although learning models have the potential to increase learning motivation in general, the effectiveness of these models requires more in-depth study with broader data.